KETERLIBATAN PEREMPUAN DALAM AKSI TERORISME DI INDONESIA - Qori?ah, Sityi Maesarotul (Sawwa: Jurnal Studi Gender, 2019)
The bomb blast in Surabaya which was an act of terrorism carried out by one family showed that women were actively involved in acts of terrorism. In the early days of the emergence of terrorism, women only acted as intermediaries, managing data through the internet network, fund collectors and driving "jihad" the husband who in fact was a terrorist. Based on this phenomenon, this paper wants to question what lies behind women's involvement in acts of terrorism? The literature review is used as a method to collect data related to women's involvement in acts of terrorism. This article will describe how women are involved in acts of terrorism. One of the successes of radicalism propaganda is actively involving women in acts of terrorism. Women as active actors in acts of terror will quickly be recognized if they show courage in jihad at the expense of their physical lives. His courage to become a 'martyr of the religion of God' was suspected to indicate the importance of a woman's piety.